Feed sorting behavior and performance of Argentinian Creole, Braford and crossbred steers during the growing and fattening phases - Della Rosa, Maria Milagros; Corva, Pablo Marcelo; Royo, Victoria; Zimerman, Maria; Bottegal, Diego Nicolas; Nasca, Jose Andres (Ediciones INTA, 2022)
Local Latin American cattle breeds are considered highly adapted to grazing systems in harsh environments, but their potential in more intensified beef production systems, particularly when compared to imported breeds, is still a matter of debate. Argentinian Creole (CRA), Braford (BRA) and Creole x Braford (CXB) steers were evaluated in the growing (Experiment 1) and fattening phases (Experiment 2). In Experiment 1, 12 animals from each genetic group were allocated after weaning to four pens and fed a total mixed ration for 57 days. In Experiment 2, six 17-month old steers of each genetic group were allocated each to a single pen and fed a high concentrate diet for 55 days. Several traits associated with animal performance, feed intake and feed sorting were recorded. Experiment 1: CRA had lower daily weight gain than the other two groups (P<0.01) and also lower feed conversion ratio than BRA (P<0.01). BRA tended to sort against long particles (> 19 mm, BRA < CXB, P = 0.03) preferring short particles (4 - 8 mm, BRA > CRA = CXB, P = 0.06). Experiment 2: CRA had lower initial body weight (P < 0.01) and the difference with BRA was maintained at the end of the experiment (P<0.01). CRA had lower initial and final back fat thickness (P < 0.01) but initial and final rib eye area did not differ among groups. Feed sorting was similar among groups (P≥0.21). Considered overall, CRA steers performed poorly compared to BRA and CXB under unrestricted feeding in both experiments.